2021
DOI: 10.1155/2021/6519063
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion Inhibits the Expression of Colonic NLRP3 through miR7/RNF183/NF-κB Signaling Pathway in UC Rats

Abstract: Background. Moxibustion has been recognized as an effective approach for ulcerative colitis, yet its mechanism is not clear. The research aimed to investigate the influence of moxibustion on the activation of NLRP3 inflammasome and its mechanism in treating ulcerative colitis by observing miR7/RNF183 inducing IκB α ubiquitination to regulate NF-κB signaling pathway in an ulcerative colitis rat model. Methods. An ulcerative colitis rat model was established by unlimited access to self-administration of 3.5% (w/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…Moreover, whether CRIZO affected the activation of NF‐κB (P65) was investigated. As anticipated, CRIZO markedly promoted phosphorylation and nuclear translocation of P65 (Figure 2C,D), which favoured the formation of NLRP3 inflammasome 17–20 …”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…Moreover, whether CRIZO affected the activation of NF‐κB (P65) was investigated. As anticipated, CRIZO markedly promoted phosphorylation and nuclear translocation of P65 (Figure 2C,D), which favoured the formation of NLRP3 inflammasome 17–20 …”
Section: Resultssupporting
confidence: 76%
“…This suggested that CRIZO could activate pyroptosis through the classical pathway but not necroptosis in HL-7702 cells.Moreover, whether CRIZO affected the activation of NF-κB (P65) was investigated. As anticipated, CRIZO markedly promoted phosphorylation and nuclear translocation of P65 (Figure2C,D), which favoured the formation of NLRP3 inflammasome [17][18][19][20].…”
supporting
confidence: 76%
See 2 more Smart Citations
“…Tissue sections were placed on glass slides and stained with H&E using standard procedures. The colon tissue's pathological changes were then observed using a light microscope [ 20 ].…”
Section: Methodsmentioning
confidence: 99%